PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING SISWA KELAS V - Nugroho, Prasetio; Sabri, Tahmid; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractA common problem in this study is whether there is an increase in the Citizenship Education learning outcomes using a model of problem based learning in class V of 41 Sungai Raya Public Schools? The purpose of this study is to improve the learning outcomes of Citizenship Education using a model of problem based learning in class V of 41 Sungai Raya Public Schools. This study uses descriptive methods with the form of classroom action research, and the nature of research is collaborative. Data collection techniques used were interview techniques, direct observation techniques, measurement techniques with data collection tools, namely observation and test sheets. The collected data is analyzed with the average calculation. This study was conducted in 3 cycles. The results obtained are the use of the problem based learning model is able to improve student learning outcomes, namely in cycle 1 obtained an average value of 74.71, and in the second cycle increased by 5.59 to 80.29, and in cycle 3 also experienced an increase of 4.12 to 84.41. With the implementation of a problem based learning model in learning civic education can improve student learning outcomes. Keywords: Learning Outcomes, Model Based Learning, and Citizenship Education